From idea to site : a project guide to creating better landscapes - Thirlwall, Claire (London : RIBA Publishing, 2020)
From Idea to Site' explores how to improve the working practices of landscape architects and therefore the quality of the design and management of our external environment. Based around the life of a project, this book puts innovation and technology at the forefront: looking at how they are changing the profession, and how these innovations might be used in the professional arena. The book also shows how landscape architecture can add to the quality and sustainability of varying construction projects, and how to make the best use of a landscape architect's skills. Including in-depth illustrated case studies from UK and international landscape schemes, the book looks at the often challenging process of getting projects to completion - `from idea to site'.
OCLC-licensed vendor bibliographic record.
Keywords: Landscape architecture; ARCHITECTURE / General; ARCHITECTURE / Landscape